2021
DOI: 10.1007/s42865-021-00041-w
|View full text |Cite
|
Sign up to set email alerts
|

Vertical profile of the clear-sky aerosol direct radiative effect in an Alpine valley, by the synergy of ground-based measurements and radiative transfer simulations

Abstract: Atmospheric aerosols play an important role in Earth’s radiative balance, directly interacting with solar radiation or influencing cloud formation and properties. In order to assess their radiative impact, it is necessary to accurately characterise their optical properties, together with their spatial and vertical distribution. The information on aerosol vertical profile is often scarce, in particular in mountainous, complex terrains. This study presents the first attempt to evaluate the shortwave aerosol dire… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 44 publications
1
3
0
Order By: Relevance
“…Thus, we use the same radiative calculations to represent the aerosol effect in the different SST scenarios. We note that the estimated RHR presented in Figure 1b aligns qualitatively in magnitude and vertical structure with observed RHR profiles from previous studies on absorbing aerosols (Z. Wang et al., 2018; Lu et al., 2020; Fasano et al., 2021; Cochrane et al., 2022).…”
Section: Methodssupporting
confidence: 85%
“…Thus, we use the same radiative calculations to represent the aerosol effect in the different SST scenarios. We note that the estimated RHR presented in Figure 1b aligns qualitatively in magnitude and vertical structure with observed RHR profiles from previous studies on absorbing aerosols (Z. Wang et al., 2018; Lu et al., 2020; Fasano et al., 2021; Cochrane et al., 2022).…”
Section: Methodssupporting
confidence: 85%
“…Previous lidar measurements in the Alps by a ground-based scanning system during VOTALP have allowed us to identify the two aerosol layers associated with inversions typically induced by local and regional orography, as well as horizontal inhomogeneities in aerosol concentrations at the opening of the Mesolcina valley near Grono, Switzerland [25]. More recently, a ground-based micropulse lidar was used in the Italian valley of Aosta to quantify, for the first time, the direct radiative effect of aerosols during two cases-one with local pollution, and one during a dust transport event in June 2019 [26]. Nonetheless, the three-dimensional distribution of pollutants was only previously investigated during POVA in the Chamonix and Maurienne valleys [17], coupling in situ airborne and lidar measurements to highlight their sources, along with urban heat island effects.…”
Section: Introductionmentioning
confidence: 99%
“…Microplastics can travel very long distances from their sources and have been detected at very high altitudes, on the order of 3 km, in the atmosphere [38,39]. Fasano et al [40] showed that even over a pristine alpine region, transported Saharan dust can increase atmospheric heating rates (HR) by more than 1 K/day (relative to aerosol-free atmosphere), and at the same time have a negative radiative effect at the top and bottom of the atmosphere. In such regions (i.e., alpine valleys) changes in atmospheric heating have an immediate impact on the climate of the slopes and are considered among the possible drivers of elevation-dependent warming (EDW) [41,42].…”
Section: Introductionmentioning
confidence: 99%